DESEMINASI TEKNOLOGI PRODUKSI BRIKET BIOARANG DARI BIOMASSA BAGI MASYARAKAT SAMBIREJO PARE KEDIRI - Suratno Lourentius; Ignatius Jaka Mulyana; Lusia Permata Sari Hartanti (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Desemination about the business of making biocharcoal briquettes from biomass waste for the people of Sambirejo Village, Pare District, Kediri Regency, East Java is one of the efforts to handle waste, efforts to find alternative energy sources and business opportunities for charcoal briquette production. The availability of biomass waste in Sambirejo Village is very abundant, but cannot be utilized. People in general have realized that the presence of waste if not handled properly will cause inconvenience to life, such as: accumulation of garbage that takes up space and unhealthy residential environment and if burned it also causes smoke that pollutes the environment. Therefore, the handling of waste and its utilization to produce charcoal briquettes need to be educated and trained for the people of Sambirejo, especially environmentalists and enthusiasts of the use of appropriate technology. For this reason, the Charcoal Briquette Team, Faculty of Engineering, Widya Mandala Surabaya Catholic University in collaboration with the Gubug Lazaris Community managed by the Priests of the Congregation of Missions intends to organize counseling on making charcoal briquettes for the people of Sambirejo Village in a scheduled and sustainable manner. From these activities, it is hoped that technology transfer will take place so that the community has the skills to produce charcoal briquettes according to the Indonesian National Standard (SNI) in terms of specifications for carbon content, volatile matter, water, ash, density and calorific value, which in the end the community has the ability to implement it in charcoal briquette manufacturing business.